PERBEDAAN PENYULUHAN TENTANG PENGETAHUAN KESEHATAN GIGI DAN MULUT MENGGUNAKAN MEDIA PERMAINAN MONOPOLI GIGI DENGAN ULAR TANGGA PADA SISWA/I KELAS II DAN III DI SDN PASAYANGAN II KECAMATAN MARTAPURA KABUPATEN BANJAR - Amelia, Yanathia Jesica; Rahmawati, Ida; Ulfah, Rasuna; Astu Rahman, Waljuni (Poltekkes Kemenkes Banjarmasin, 2025)
The proportion of dental and oral problems in Banjar Regency is 52.29%, indicating that dental and oral health problems in South Kalimantan Province, especially in Banjar Regency, are still very high. Oral and dental health is often ignored and is not a top priority in health matters, especially for elementary school children. This research aims to find out differences in counseling about dental and oral health knowledge using the game media dental monopoly with ‘ular tangga’ in class II and III students at Pasayangan II Elementary School, Martapura District, Banjar Regency. Type of research with experiments pseudo research using two group pretest-posttest design. The research sample was 37 students in class II and III, taken sample using total sampling technique. The results showed the average value of knowledge before counseling using the dental monopoly game media was 10.26 and after that was 12.42. Meanwhile, the average value of knowledge before counseling using the ‘ular tangga’ game media was 9.83 and after that was 12.00. The research result used the Independent Sample T-test obtained ρ=0.985 > α=0.05 so that Ho is accepted and Ha is rejected. Conclusion, there was no difference in counseling about dental and oral health knowledge using the game media dental monopoly with ‘ular tangga’ in class II and III students at Pasayangan II Elementary School, Martapura District, Banjar Regency. Suggestion, there needs to be continuous promotive activities such as counseling using the interesting game media in order to help students understand dental and oral health problems